Where there is danger - Jurgenson, Luba, 1958-; Sopher, Meredith, 1992- (Boston : Academic Studies Press, 2019)
"Writer, professor, translator and editor Luba Jurgenson lives between two languages--her native Russian and her adopted French. She recounts the coexistence of these two languages, as well as two bodies and two worlds, in an autobiographical text packed with fascinating anecdotes. Living bilingually can be uncomfortable, but this strange in-between state can equally serve as a refuge and inspire creativity. Jurgenson sheds light on this little-explored territory with lively prose and a keen awareness of her historical and literary context. Language, identity, translation, and the self: all are intertwined. The ceaseless journey of bilingualism is at last revealed"--Provided by publisher.
Frontmatter -- Contents -- 1. Conversation in the Mountains -- 2. The Third-to-Last -- 3. The Sidewalk Across the Street -- 4. Mouths, Rivers, and the Letter R -- 5. The Sidewalk Across the Street, Part 2 -- 6. Forgetting Babel -- 7. Stumbling Block -- References -- Index
Includes bibliographical references.
Print version record and CIP data provided by publisher; resource not viewed.
eBooks on EBSCOhost
Keywords: Jurgenson, Luba, -- 1958-; Jurgenson, Luba, -- 1958-; Translators -- France -- Biography; Russian language -- Translating into French; Translating and interpreting; Authors, French -- 21st century -- Biography; Authors, French; Écrivains français -- 21e siècle -- Biographies; Russe (Langue) -- Traduction en français.; LITERARY COLLECTIONS -- Essays; LITERARY COLLECTIONS / Essays; Authors, French; Russian language -- Translating into French; Translating and interpreting; Translators; France; Translators -- France -- Biography; Russian language -- Translating; Translating and interpreting; Authors, French -- 21st century -- Biography; Bilingualism; Language and culture; 2000-2099; Biographies